A Comparative Study of Financial Literacy among Undergraduate Management and Humanities Students of Pokhara University - Adhikari, Nischal; Chhetri, Shanti Devi; Poudel, Rakshya; Devkota, Lokesh; Pandey, Shristi (KMC Journal, 2025)
This study aims to assess and compare the level of financial literacy among undergraduate Management and Humanities students of Pokhara University. Specifically, it evaluates differences in financial knowledge, financial skills, and financial attitudes between students from these two academic disciplines. This descriptive, cross-sectional, and comparative study assessed the financial literacy of 327 undergraduate students from Pokhara University’s Management and Humanities programs using convenience sampling. Data were collected with a verified financial literacy questionnaire based on OECD guidelines. Independent t-tests compared financial literacy between disciplines, one-way ANOVA examined differences by year of study, and Cohen’s d measured effect size. A radar chart visually displayed group variations. The findings revealed a significant difference in financial knowledge, skills, and overall financial literacy between Management and Humanities students, with management students performing better in all areas, although the effect sizes were small. However, financial attitude did not differ between the two faculties. Financial literacy, knowledge, skills, and attitude significantly varied by year of study, with fourth-year students demonstrated higher score than those in earlier years. No significant differences were found in financial knowledge, skills, and overall financial literacy between male and female respondents, but females exhibited a higher financial attitude than males. The findings highlight the need for targeted financial literacy programs tailored to each faculty’s needs. While financial attitudes are similar, fostering positive financial behaviour is crucial for long-term well-being. A holistic approach, incorporating knowledge, skills, and attitudes, is essential, with faculty-specific solutions to prepare students for financial success. These insights can guide policymakers, educators, and financial institutions in developing effective programs to improve students’ financial preparedness.